Game Based Learning Sebagai Media Pengoptimalan Keterampilan 4C - Mukhammad Nur Muzakka; Ninda Aulia; Sabilatul Aisyah Putri; Muhammad Nofan Zulfahmi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
21st century education demands mastery of 4C skills (Critical Thinking, Collaboration, Creativity, Communication) as an important foundation in facing global challenges. Game Based Learning (GBL) offers an innovative learning approach that integrates game elements to support the development of these skills. This study aims to analyze GBL in optimizing students' 4C skills through the Systematic Literature Review (SLR) method. Data were collected from relevant articles and books published between 2020–2024 using keywords such as learning media and 4C skills. The results of the study indicate that GBL has a significant impact on improving skills in critical thinking, collaboration, creativity, and communication in students. This study also shows that GBL creates an interactive and fun learning environment that can strengthen students' learning motivation. GBL is an effective learning medium to support the development of 4C skills. Wider implementation is expected to encourage students to become competent individuals who are ready to face the challenges of the globalization era.